Pengaruh Pengetahuan Investasi, Kebijakan Modal Minimal Investasi, dan Pelatihan Pasar Modal Terhadap Minat Investasi - Sindy Utami; Hwihanus Hwihanus (BADAN PENERBIT STIEPARI PRESS, 2024)
This research aims to determine the influence of investment knowledge, minimum capital policies, and capital market training on students' investment interest. Researchers want to know the factors that influence students' investment interest. Research data was obtained directly through a questionnaire that was distributed to 96 respondents. The sampling method uses purposive sampling with the criteria that the respondent is an active student at the university concerned and has attended capital market training or education. The analytical tool used in this research is Smart PLS version 4 software. The results of the research show that Investment Knowledge has a positive and significant effect on students' Investment Interest. (H1); The minimum capital policy has a positive and insignificant effect on students' investment interest (H2); Capital Market Training has a positive and insignificant effect on students' Investment Interest. (H3).